2009
DOI: 10.1111/j.1365-2443.2008.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

AMP‐activated protein kinase phosphorylates glutamine : fructose‐6‐phosphate amidotransferase 1 at Ser243 to modulate its enzymatic activity

Abstract: Glutamine : fructose-6-phosphate amidotransferase 1 (GFAT1) was identified as a protein phosphorylated in glucose-deprived cells by immunoprecipitation using the anti-phospho Akt substrates (PAS) antibody, which recognizes the phosphorylation motif site by AMP-activated protein kinase (AMPK), followed by mass fingerprinting analysis. Glucose depletion-induced phosphorylation of endogenous GFAT was potentiated by 2-deoxyglucose (2-DG), an AMPK activator, and the 2-DG-stimulated phosphorylation of FLAG-tagged GF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 37 publications
6
80
1
Order By: Relevance
“…90 Mechanistically, adiponectin stimulates AMPK, a kinase that suppresses energy-consuming pathways such as hexosamine and cholesterol biosynthesis. [91][92][93] We have found that AMPK stimulation improves GLUT4-mediated glucose transport and ABCA1/ ApoA1-mediated cholesterol efflux from insulin-resistant 3T3-L1 adipocytes via lowering membrane cholesterol levels. 41 This factor was not found to differ before and after administration of pitavastatin in overall analysis of all the subjects.…”
Section: Review Diabetesmentioning
confidence: 98%
“…90 Mechanistically, adiponectin stimulates AMPK, a kinase that suppresses energy-consuming pathways such as hexosamine and cholesterol biosynthesis. [91][92][93] We have found that AMPK stimulation improves GLUT4-mediated glucose transport and ABCA1/ ApoA1-mediated cholesterol efflux from insulin-resistant 3T3-L1 adipocytes via lowering membrane cholesterol levels. 41 This factor was not found to differ before and after administration of pitavastatin in overall analysis of all the subjects.…”
Section: Review Diabetesmentioning
confidence: 98%
“…The anti-PAS antibody has been used to screen for growth-factor-regulated and nutrient-regulated phosphoproteins, which include not only the actual substrates of Akt but also substrates of S6K and AMP-activated protein kinase in mammalian cells (Eguchi et al, 2009;Kane et al, 2002;Manning et al, 2002;Miyamoto et al, 2008). To examine nitrogen-regulated phosphoproteins by using the anti-PAS antibody, fission yeast cells were cultured in medium in the presence or absence of ammonium as the sole nitrogen source.…”
Section: Phosphorylation Of P27 Recognized By Anti-pas Antibody Respomentioning
confidence: 99%
“…In fact, chronic glutamine supplementation to trained rats has shown to increase muscle GSH contents and GS at the same time that it has enhanced HS response [49]. Corroborating this assumption is the fact that the activation of GFAT depletes intracellular glucose stores [239]. Oppositely, GSH depletion, per se, increases OGT gene expression leading to O-GlcNAcylation of different regulatory proteins [251], thus strongly suggesting that HBP has a short-loop positive feedback system devoted to assist in cytoprotection via HS response soon as some redox threatening situation is ongoing.…”
Section: Glutamine Metabolism and Its Importance For The Heat Shock Rmentioning
confidence: 99%
“…HBP is a nutrient-sensing pathway [226] that presents multiple connections with energy metabolism, not only with glycogen synthesis [219]. AMPK, which occupies a central position in metabolic regulation in order to avoid inflammatory dysregulation, phosphorylates and inhibits GFAT1, the flux-generating step of HBP, thus allowing for the downregulation of such a shunt from the glycolysis under low glucose situations [239]. Conversely, chronic hexosamine flux stimulates fatty acid oxidation by activating AMPK [240].…”
Section: Glutamine Metabolism and Its Importance For The Heat Shock Rmentioning
confidence: 99%
See 1 more Smart Citation